The level of communities’ awareness towards human trafficking / Norita Mohd Yusoff - Mohd Yusoff, Norita (Faculty of Business and Management, 2012)
Nowadays, the issues of Human Trafficking in our country were highly increased from time to time therefore a study towards findings the suitable strategies for our country had been carried out. The purpose of the study is to identify the level of community’s awareness towards human trafficking, to determine the factors contribute to level of community’s awareness towards human trafficking and to examine the most effective factor contribute to the level of community’s awareness towards human trafficking. A good research design will ensure that the marketing research project is conducted effectively. The target, sampling size for this study is 100 respondents where the questionnaires were randomly distributed to Negeri Sembilan area. For this study, the non-probability sampling technique which is convenient sampling has been chosen. Moreover, computer programs have been developed to simplify and ease the research tabulation and analysis task. One of the most accurate and dependable statistical analysis packaging is Statistical Package for Social Science (SPSS). Included in this package are the procedure of frequency, descriptive and correlation the finding from the study is to found whether this study achieved the objective or not.